Aspectos clínico-epidemiológicos asociados a la evolución de los pacientes hospitalizados por quemaduras en el Hospital Regional de Loreto 2018 - 2022 - Angulo Perea, Jean-Andrehass de Jesús (2024)
Objective: Determine the clinical-epidemiological aspects related to the evolution of patients treated in the Burn Unit of the Regional Hospital of Loreto during the years 2018-2022. Methods: A descriptive cross-sectional and retrospective study was conducted with 248 patients hospitalized for burns from 2018 to 2022, whose data were collected from medical records in an instrument adapted from the National Institute of Child Health, the data were processed in the statistical software SPPPS version 22, subjecting the nominal variables to chi-square and calculating the association with Odds Ratio. Results: The most affected age group was 1-5 years (41.1%), sex was predominantly male (63.3%), the population was more frequently from urban areas (82.7%). The level of education was unknown in 52% of the cases. The most frequent causal agent was hot liquid (60.5%). Second-degree burns were the most frequent (87.5%). More than half of the population used antibiotics (53.6%). 2% presented sepsis, 1.6% shock, 4.6% inhalation injury. 85.9% presented favorable evolution. Conclusions: The frequency of burns in underage was 2 times higher compared to adults. The most common causal agent was hot liquids in home environments. Large burns represented the group with the greatest need for ventilatory support, of which 75% presented shock. Inhalation injury was associated with 24.89 times the risk of death.